2020
DOI: 10.3389/fimmu.2020.552613
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Implicated in Carbon Nanotube-Induced Lung Inflammation

Abstract: Inflammation is a tissue response to a variety of harmful stimuli, such as pathogens, irritants, and injuries, and can eliminate insults and limit tissue damage. However, dysregulated inflammation is recognized as a cause of many human diseases, exemplified by organ fibrosis and cancer. In this regard, inflammation-promoted fibrosis is commonly observed in human lung diseases, such as idiopathic pulmonary fibrosis and pneumoconiosis. Carbon nanotubes (CNTs) are a type of nanomaterials with unique properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 89 publications
(136 reference statements)
1
18
0
Order By: Relevance
“…Creating and developing new nanobiotechnological products are urgent endeavors when the goal is to provide new types of immunotherapies that generate and/or improve an immune response. 12,66,67 Therefore, the safety and development of new materials used to restore and modulate the immunological systems in patients affected by several diseases/infections are realities. 68 Nanomaterials have been widely used in immunotherapies for immunomodulation.…”
Section: Immune Activation By Carbon Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…Creating and developing new nanobiotechnological products are urgent endeavors when the goal is to provide new types of immunotherapies that generate and/or improve an immune response. 12,66,67 Therefore, the safety and development of new materials used to restore and modulate the immunological systems in patients affected by several diseases/infections are realities. 68 Nanomaterials have been widely used in immunotherapies for immunomodulation.…”
Section: Immune Activation By Carbon Nanotubesmentioning
confidence: 99%
“…93 f-CNTs induce profound modulation of inflammatory molecules at the transcriptome level, and the molecular pathways activated by these nanotubes include TLR, IL-6, DC maturation, TNF, NF-kB, and T-h 1-chemokine pathways (CXCR3 and CCR5 ligand pathways) (Figure 3A). 66 Therefore, T-cell anti-CD3 complex antibodies immobilized on SWCNTs exhibit effective cellular activity with the presentation of high-density protein stimuli. 94,95 Results have demonstrated the potential benefits of CNTs as delivery systems for vaccines against different diseases, including cancer.…”
Section: Advances In the Use Of Carbon Nanotubes As Immunotherapeutic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is a tissue response to a variety of harmful stimuli, such as pathogens, irritants, and injuries, and can eliminate tissue damage. However, dysregulated inflammation is a recognized cause of many human diseases, exemplified by organ fibrosis and cancer [15]. Etiologic studies revealed close relationship between chronic inflammation and lung cancer induced by inhalation of dust particles, such as silica and asbestos.…”
Section: Introductionmentioning
confidence: 99%
“…However, inappropriately activated in ammation can become pathogenic in ammatory diseases [7]. In ammatory storm could be spotted in patients suffering from AKI with a large number of macrophages in ltrated in kidney tissues [8].…”
Section: Introductionmentioning
confidence: 99%